Holocene glacial activity in Barilari Bay, west Antarctic Peninsula, tracked by magnetic mineral assemblages: Linking ice, ocean, and atmosphere (Dataset) ... - Reilly, Brendan T.; Natter, Carl J.; Brachfeld, Stefanie A. (Magnetics Information Consortium (MagIC), 2020)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Holocene glacial activity in Barilari Bay, west Antarctic Peninsula, tracked by magnetic mineral assemblages: Linking ice, ocean, and atmosphere ...